Feminist Epistemology and The Search For Liberating Knowledge - Hidayat, Rachmad (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2018)
This paper discusses problems in dealing with masculinized knowledge and scientific enterprises, and seeks alternative epistemological strategies in achieving liberating and un-dominated knowledge production. A general problem with